La narración oral en la Educación Secundaria Obligatoria: una propuesta didáctica - Sbriziolo , Carola (Huarte de San Juan. Filología y Didáctica de la Lengua, 2017)
Oral competence is a very important aspect of language; however, it does not receive due attention in the academic research and in the classroom research. The modalities of discourse that are usually studied and practiced are almost always argumentation or exposition, but as far as the narrative is concerned, there are few studies. This work aims, first, to outline the theoretical coordinates of narrative oral texts, and then proposes a teaching sequence to improve the narrative oral competence in 3º ESO students. After experiencing the sequence in a classroom, it has been possible to extract data, make a qualitative study of the successes and difficulties of the students.
Keywords: Orality; narrative; teaching secuence; classrrom; Obligatory Secondary Education